Dpe2/phs1 revealed unique starch metabolism with three distinct phases characterized by different starch granule numbers per chloroplast, allowing insights into the control mechanism of granule number regulation by gene co-regulation and metabolic profiling - Li, Xiaoping; Apriyanto, Ardha; Castellanos, Junio Flores; Compart, Julia; Muntaha, Sidratul Nur; Fettke, Joerg (Frontiers in Plant Science, 2022)
An Arabidopsis mutant lacking both the cytosolic Disproportionating enzyme 2 (DPE2) and the plastidial Glucan phosphorylase 1 (PHS1) revealed a unique starch metabolism. Dpe2/phs1 has been reported to have only one starch granule number per chloroplast when grown under diurnal rhythm. For this study, we analyzed dpe2/phs1 in more detail following the mutant development, and found that it showed three distinct periods of granule numbers per chloroplast. In young plants, the starch granule number was similar to that in Col-0 at first, and then decreased significantly, down to one or no granule per chloroplast, followed by an increase in the granule number. Thus, in dpe2/phs1, control over the starch granule number is impaired, but it is not defective in starch granule initiation. The data also indicate that the granule number is not fixed, and is regulated throughout plant growth. Furthermore, the chloroplasts also revealed alterations during these three periods, with a partially strong aberrant morphology in the middle phase. Interestingly, the unique metabolism was perpetuated when starch degradation was further impaired through an additional lack of Isoamylase 3 (ISA3) or Starch excess 4 (SEX4). Transcriptomic studies and metabolic profiling revealed the co-regulation of starch metabolism-related genes and a clear metabolic separation between the periods. Most senescence-induced genes were found to be up-regulated more than twice in the starch-less mature leaves. Thus, dpe2/phs1 is a unique plant material source, with which we may study starch granule number regulation to obtain a more detailed understanding.